A Pilot Randomized Controlled Trial of the Feasibility of a Multicomponent Delirium Prevention Intervention Versus Usual Care in Acute Stroke. Issue 1 (January 2017) - Rice, Karen L.; Bennett, Marsha J.; Berger, Linley; Jennings, Bethany; Eckhardt, Lynn; Fabré-LaCoste, Nicole; Houghton, David; Vidal, Gabriel; Gropen, Toby; Diggs, Erica; Barry, Erin; St. John, Jennilee; et al.
Abstract : Background: Delirium after acute stroke is a serious complication. Numerous studies support a benefit of multicomponent interventions in minimizing delirium-related complications in at-risk patients, but this has not been reported in acute stroke patients. The purpose of this study was to explore the feasibility of conducting a randomized (delirium care) versus usual standardized stroke care (usual care) in reducing delirium in acute stroke. Objective: This pilot study assessed the feasibility of (1) enrollment within the 48-hour window when delirium risk is greatest, (2) measuring cognitive function using the Montreal Cognitive Assessment, (3) delivering interventions 7 days per week, and (4) determining delirium incidence in stroke-related cognitive dysfunction. Methods: A 2-group randomized controlled trial was conducted. Patients admitted with ischemic and hemorrhagic strokes and 50 years or older, English speaking, and without delirium on admit were recruited, consented, and randomized to usual care or delirium care groups. Results: Data from 125 subjects (delirium care, n = 59; usual care, n = 66) were analyzed. All Montreal Cognitive Assessment subscales were completed by 86% of subjects (delirium care, mean [SD], 18.14 [6.03]; usual care, mean [SD], 17.61 [6.29]). Subjects in the delirium care group received a mean of 6.10 therapeutic activities (range, 2–23) and daily medication review by a clinical pharmacist using anticholinergic drug calculations. Delirium incidence was 8% (10/125), 3 in the delirium care group and 7 in the usual care group. Conclusion: Findings support the feasibility of delivering a multicomponent delirium prevention intervention in acute stroke and warrants testing intervention effects on delirium outcomes and anticholinergic medication administration.